Concentration Of Spodumene From North Carolina Pegmatite Ores (PRIPRINT 77-H-382) - Immo H. Redeker (Society for Mining, Metallurgy & Exploration, 1977)
The Kings Mountain area of North Carolina is the lithium pegmatite center of the U.S., if not of the whole world. We have two spodumene and by-product mineral producing companies, Lithium Corp. of America, and Foote Mineral Company. We also have Kings Mountain Mica and Kings Mountain Silica Companies producing mica. feldspar, quartz and clay from weathered pegmatites in that area. Figure 1 gives the location of the spodumene pegmatite area in North Carolina. The two spodumene producers mine typical pegmatite ore in open pits after removing amphibolite or mica schist overburden which is sold to aggregate producers. The ore reserves are discussed elsewhere in this session. They are in the order of plus 50 million tons but not unlimited. 1.2 The major minerals found and concentrated from the North Carolina spodumene pegmatite ores are tabulated on Table 1.